Unusual genomic rearrangements in introns 1 and 22 of the F8 gene - Zimmermann, M. A.; Oldenburg, J.; Müller, C. R.; Rost, S. (Hämostaseologie, 2011)
Intron 1 and intron 22 inversions, two large rearrangements of the factor VIII gene, are generally associated with a severe phenotype of haemophilia A and a high risk of inhibitor formation. In several haemophiliacs, diagnostic analyses for detection of these inversions revealed unusual band patterns. Upon further examination, different copy number variations were detected in the factor VIII gene of these patients by multiplex ligationdependent probe amplification (MLPA). Since these duplications or deletions alone could not sufficiently explain the abnormal band patterns of the first analyses, we assumed a combination of intron 1 or intron 22 inversions together with a copy number variation.Result We could confirm this hypothesis by specific long range PCRs but a detailed characterization of the breakpoints and the mechanisms for these complex rearrangements have yet to be elucidated.
Keywords: Factor VIII; intron 1 inversion; intron 22 inversion; copy number variations